2020
DOI: 10.1007/s10900-020-00919-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of the Vietnamese as Key Factors in Controlling COVID-19

Abstract: This study aimed to describe knowledge, attitudes, and practices (KAP) in controlling COVID-19 and some related factors among the Vietnamese population in 2020. A cross-sectional study was conducted involving 1999 participants aged 18-59 years old, through an online questionnaire. The results showed that 92.2% of the participants had a high knowledge level regarding COVID-19 prevention measures, 68.6% had a positive attitude toward COVID-19 prevention measures, and 75.8% practiced all six measures for preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
53
6
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 8 publications
(11 reference statements)
24
53
6
6
Order By: Relevance
“…Disease awareness in our study (76.2%) was lower than that reported by a contemporaneous study in Hubei Province, China (90%) 62 and another one from Vietnam (92.2%). 28 This difference may be due to the gap between self-assessed and tested knowledge level. Participants in our study might have felt uncertain regarding their disease awareness during the pandemic, which could have lowered the self-evaluation of their knowledge level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease awareness in our study (76.2%) was lower than that reported by a contemporaneous study in Hubei Province, China (90%) 62 and another one from Vietnam (92.2%). 28 This difference may be due to the gap between self-assessed and tested knowledge level. Participants in our study might have felt uncertain regarding their disease awareness during the pandemic, which could have lowered the self-evaluation of their knowledge level.…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ disease awareness was negatively correlated with the public emergency psychological state, which is supported by previous studies. 8 , 63 Documented studies have shown that knowledge is related to more preventive behaviors 28 , 64 and the involvement in these behaviors and various strategies can facilitate the maintenance of psychological well-being. Additionally, insufficient disease awareness can lead to the perpetuation of misinformation and superstitious beliefs, which not only affect the correct implementation of preventive measures, but also aggravate public panic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions aimed at reducing psychological burden during COVID-19 depend in part on the repetitive dissemination of relevant information, total coordination of multiple health sectors, and promotion of altruistic behavior ( 18 , 28 ). Having sufficient knowledge about the virus is necessary for epidemiological purposes and may correlate with increases in positive attitudes toward the virus ( 26 ). Moreover, this can be translated to health literacy, which can lower the likelihood of depression and increase measurements of quality of life in outpatients suspected of having COVID-19 symptoms ( 22 ).…”
Section: Considerations For Mental Healthmentioning
confidence: 99%
“…Moreover, this can be translated to health literacy, which can lower the likelihood of depression and increase measurements of quality of life in outpatients suspected of having COVID-19 symptoms ( 22 ). The Vietnamese government's rigorous campaign to combat misinformation alongside consistent equivocal messages about the virus may have protected against the effects of quarantine, facilitating optimistic attitudes and trust in the government, reducing catastrophic appraisals of health ( 18 , 26 ). Communication by the government was laden with surprisingly effective war rhetoric ( 9 , 25 ).…”
Section: Considerations For Mental Healthmentioning
confidence: 99%